Perancangan Strategi Bisnis House Tapis Citra (HTC) Berbasis Business Model Canvas (BMC) dan Analisis SWOT - Abmar, M Rafi Chairani; Suharto, Suharto; Meliana, Dita (Fakultas Teknik Universitas Tulang Bawang, 2026)
House Tapis Citra (HTC) is a small and medium enterprise (SME) in Lampung engaged in traditional tapis fabric craftsmanship, which holds high cultural and economic value. However, it faces challenges in marketing strategy, unclear market segmentation, and weak business management. This study aims to formulate a comprehensive business development strategy using the Business Model Canvas (BMC) and SWOT analysis. The results show that HTC is positioned in Quadrant I (aggressive strategy) with an IFAS score of +2.131 and an EFAS score of +0,669. Recommended strategies include product innovation, digital marketing through social media and marketplaces, diversification of distribution channels, and strategic partnerships. These strategies are expected to enhance competitiveness, expand market reach, and support cultural preservation as well as the creative economy in Lampung. Keywords: Business Development Strategy, Business Model Canvas (BMC), House Tapis Citra (HTC), SWOT.